The Correlation Between The Habit Of Listening To English Songs and Vocabulary Mastery of Student of English Education Department of Universitas Muhammadiyah Yogyakarta. - Nurul Maziyah (PBI 14 UMY 004, 2014)
Vocabulary is the core component of language. It will help the students for mastering the four skills in language namely listening, speaking, reading and writing. Vocabulary is the key for them to comprehend texts. The students are able to communicate through writing and oral communication. Listening is the key to successful learning, or at least the primary source of language experience. Listening to English songs is one of approaches to increase their vocabulary. Trough listening to the songs, students do not only improve their listening skill but also improve vocabulary and pronunciation. Songs provides many features such as lyrics, repetition, enjoyable and authentic material.In this thesis, the objectives of the study are (1) to investigate the habit of listening to English songs of students of English Education Department; (2) to investigate the vocabulary mastery of students of English Education Department; (3) to investigate the correlation between the habit of listening to English songs and the vocabulary mastery of students of English Education Department of UniversitasMuhammadiyah Yogyakarta. This research is a quantitative correlation design with two variables. The first variable is habit on listening to English songs. The second variable is vocabulary mastery. The instruments are questionnaire and vocabulary test. Those instruments are to measure habit on listening to English songs and vocabulary mastery of the students of English Education Department of UniversitasMuhammadiyah Yogyakarta. The results of the questionnaire and vocabulary mastery are cultivated using SPSS 15. The result of the questionnaire and vocabulary test show that habit on listening to English songs and vocabulary mastery of the students of English Education Department of UniversitasMuhammadiyah Yogyakarta is in low category. The computations show that the coefficient correlation between habit on listening to English songs and vocabulary mastery is 0.201. So that it can be conclude that there is a correlation between habit on listening to English songs and vocabulary mastery.